2020
DOI: 10.1371/journal.pone.0226313
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between maximal incremental and high-intensity interval exercise performance in elite athletes

Abstract: This descriptive study aimed to explore the physiological factors that determine tolerance to exertion during high-intensity interval effort. Forty-seven young women (15-28 years old) were enrolled: 23 athletes from Taiwan national or national reserve teams and 24 moderately active females. Each participant underwent a maximal incremental INC (modified Bruce protocol) cardiopulmonary exercise test on the first day and high-intensity interval testing (HIIT) on the second day, both performed on a treadmill. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…To our knowledge, this phenomenon has not been reported in studies with a similar protocol (i.e., HIIE including a fixed number of repetitions). However, other studies using HIIE performed until exhaustion have reported higher VO 2 values during HIIE than during a maximal incremental test (Billat et al 2000 ; Chang et al 2020 ).…”
Section: Discussionmentioning
confidence: 87%
“…To our knowledge, this phenomenon has not been reported in studies with a similar protocol (i.e., HIIE including a fixed number of repetitions). However, other studies using HIIE performed until exhaustion have reported higher VO 2 values during HIIE than during a maximal incremental test (Billat et al 2000 ; Chang et al 2020 ).…”
Section: Discussionmentioning
confidence: 87%
“…During the fast decrease of oxygen uptake the hemoglobin affinity to oxygen progressively declines due to the decreasing number of free hemoglobin binding sites. This saturation causes a plateauing of Sm (%) in recovery (compare Figure 2B and Chang et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…Acceleration of autonomic cardiovascular system recovery after exercise has advantages. First, faster HR recovery brings a larger heart rate reserve for the next bout, which helps maintain performance on the court (Chang et al, 2020). Second, ventricular arrhythmia tends to occur at a high sympathetic tone and during the recovery phase more than during exercise (Gooch and McConnell, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…When recovery time is insufficient, the performance may decline as the game progresses. Therefore, fast post-exercise recovery is helpful for the players to maintain high performance on the court (Chang et al, 2020). Acceleration of autonomic cardiovascular system recovery after exercise also has other ad-vantages.…”
Section: Introductionmentioning
confidence: 99%